Cone–beam computed tomographic analysis of maxillary and mandibular changes after high condylectomy combined with orthodontic treatment for active unilateral condylar hyperplasia. Issue 8 (October 2018) - Wu, C.; Meng, Q.; Deng, M.; Cai, H.; Ke, J.; Long, X.
Abstract: Our aim was to evaluate the efficacy of high condylectomy combined with orthodontic treatment for active unilateral condylar hyperplasia in 25 affected patients, by an analysis of the maxillary and mandibular changes on cone–beam computed tomography (CT). High condylectomy was the sole operative treatment. Variables that reflected the canting of the occlusal plane, the height of the maxillary complex, the buccolingual angulation of the maxillary first molar, the height of the ramus, the total length of the mandible, and the deviation of the chin were measured and compared between the two sides and between time intervals: preoperatively (T1) and the end of treatment (T2). The differences between time intervals in the deviation of the chin (p < 0.001) and the canting of the occlusal plane (p < 0.001) were significant, but there were no significant differences in the height of the ramus (p = 0.476) and the total length of the mandible (p = 0.838) between the affected and unaffected sides at T2. There were significant differences between time intervals in the buccolingual angulation on the unaffected side and the height of the maxillary complex on the affected side (p < 0.001). Facial asymmetry was corrected and the occlusal plane was improved. In conclusion, high condylectomy as the sole operative treatment combined with orthodontic treatment can provide an alternative method for correction of facial asymmetry associated with active unilateral condylar hyperplasia.